Polish and Czech “literary reciprocity” in the second half of the 19th century: Eliza Orzeszkowa’s reception by the Czechs and Karolina Světlá’s reception by the Poles - Fournier Kiss, Corinne (Poznańskie Studia Slawistyczne, 2012)
The aim of the article is to describe the extraordinarily animated and extensive relationships between Polish and Czech literature in the second half of the 19th century. Literary correspondence is extremely clearly revealed with regard to the Czech writer Karolina Světla and her reception in Poland and the Polish writer ElizaOrzeszkowa together with her reception in Czech. The article attempts to indicate the reasons for their popularity in these neighbouring countries in the last decades of the 19th century. Thus the subsequent reflection explores a shared viewpoint of both writers concerning national questions, combined with the necessity of women’s liberation, including their accessibility to education. By exploring the critical possibilities of literature, Světla and Orzeszkowa were exposing the imperfections of their own nations regarding patriotism and emancipation. At the same time, it is worth stressing that both writers regarded their neighbouring nation as a model.